Miss congeniality [videorecording (DVD)] - Petrie, Donald; Bullock, Sandra; Caine, Michael; Bratt, Benjamin, 1963-; Bergen, Candice, 1946-; Shatner, William; Hudson, Ernie (Warner Home Video, 2001)
Her legs are waxed, her lips are glossed, her gun is ready. FBI agent Gracie Hart is going undercover as one of the hopefuls to be the next Miss United States. But Gracie, whose idea of a fashion accessory is the set of handcuffs she slaps onto lawbreakers, doesn't have a beauty pageant bone in her body.